(untitled) (ModaPalavra e-periódico, 2019)
The beautiful body sense effects are socially and historically progressive, marked by cultural, social, class, political or religious stereotypes. The media and fashion also have a strong influence on the beauty standards imposed. The media appears as a privileged place of constitution, formulation and circulation of the senses of what can be a beautiful body or not, legitimating institutions that determine what can and can’t be said/shown in different spaces. Fashion, in turn, is a market space. Thus, the plus size movement emerges as a need for acceptance and interaction of fat bodies in fashion. However, the condition of the fat body does not change, appointments are changed to produce an effect of which this body is possible, but it remains impossible within the standardization aspects of institutions